CHALLENGES FACED BY TEACHERS WHILE TEACHING VISUAL AND HEARING-IMPAIRED STUDENTS AT SCHOOL LEVEL - Hina Akbar, Hafiza Gulnaz Fatima, Ibtasam Thakur (JIE, 2024)
The research explores the challenges faced by teachers while teaching students in visual and hearing impairment schools. For this Study, a qualitative method was used. The data was collected by the researchers by conducting the interviews of 10 visuals and hearing impairment schoolteachers. 5 teachers were selected from visual impairment school and 5 teachers were selected from hearing impairment school. The data was obtained from the semi-structure interviews, transcribed, and analyzed through thematic analysis using open and axial coding technique. The findings suggested that the teachers did face challenges while teaching visual and hearing impairment students. Several facts were identified that could ease these teachers' challenges. These challenges include behavior issues, teaching material issues, emotional issues and methodology issues.